Pemberdayaan Kelompok Penggerak Pariwisata (Kompepar) dalam Pengembangan Potensi Wisata Bogor Selatan - Eneng Tita Tosida; Indra Gunawan; Fredi Andria (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2015)
Tourism potential in South Bogor spreads in several villages, including the Pamoyanan, Empang, and Cikaret Village. Kompepar is driving tourism groups that take part in the management of tourism in South Bogor. The tourism in the area has not been fully managed due to the ability of tourism management still minimal. Therefore it is necessary to empowering Kompepar through training identification of potential tourism travel, tour packaging, and making proposals for procurement activities/tour supporting infrastructure. Models of activities carried out by training, mentoring, and on going monitoring, through tutorials, discussion, lab (field surveys and interviews) as well as presentations. The training divided in to three steps, with the strategy implemented in door training (in class) and mobile partners to target areas. The results show the training participants are able to make an identification of potential training products such as travel, tour packages, and a simple proposal. The quality of training results have not shown good results. This constrained the ability of the participants were minimal basis for knowledge about and some of the participants have not mastered basic computer. Therefore the process of assisting and monitoring is done continuously and in parallel, for each group is accompanied by one or two instructors. Empowerment followed by media online optimization via engagement KIM South Bogor, by way of training and mentoring to load the identification of potential sites and travel packages to www.wisatabogorselatan.com. Empowerment comes with mentoring and facilitating Kompepar in propose the proposals to the relevant stakeholders.